Non-antibiotic approaches to combat motile Aeromonas infections in aquaculture: Current state of knowledge and future perspectives - Le Thanh Dien; Thao Phuong Huynh Ngo; Thao V. Nguyen; Kayansamruaj, P.; Salin, K.R.; Mohan, Chadag V.; Rodkhum, Channarong; Ha Thanh Dong (Wiley, 2023)
Inland aquaculture contributed by three major fish groups, including carps, tilapias, and catfish plays a vital role in global food security and nutrition, particularly in low and middle-income countries. However, the sustainable development of this sector is hampered by disease epidemics, especially those caused by bacteria such as Aeromonas species. At least eight pathogenic motile Aeromonas species (A. hydrophila, A. veronii, A. jandaei, A. caviae, A. sobria, A. bestiarum, A. dhakensis and A. schubertii) have been reported in aquaculture with some causing up to 100% mortality during disease outbreaks. Simultaneously, emerging multidrug-resistant Aeromonas due to a long-inappropriate use of antibiotics is alarming and highlights a global public health concern and negative socioeconomic impacts. Here, we provide a comprehensive overview of motile Aeromonas infections, antibiotic use and antimicrobial resistance of Aeromonas species. This contribution also highlights the non-antibiotic approaches (the solutions for preventing or treating of bacterial diseases without resorting to antibiotic use) to control motile Aeromonas infections. In addition to the current state of knowledge and limitations of each prophylaxis/therapy, perspectives for future research are discussed critically, including oral/immersion multivalent vaccines, microencapsulated synbiotics, exogenous metabolites, and novel lytic bacteriophage cocktails. Some emerging applicable nanotechnology themes such as nanovaccines, nanobioactive compounds, and nanobubbles are also included in this review. In summary, combating motile Aeromonas infections in aquaculture, including multidrug-resistant aeromonads, as well as other bacterial diseases, is a lengthy battle that requires a strategic combination of multiple non-antibiotic approaches coherent with the One Health philosophy.